RETRACTED: Improving the methodological basis of assessing the competitiveness of a tourist region: the case of the regions of the Republic of Uzbekistan - Sobirov Bobur; Yekimov Sergey; Kreckova Renata (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 420, 00001 (2023), https://doi.org/10.1051/e3sconf/202342000001